Fractalkine – a local inflammatory marker aggravating platelet activation at the vulnerable plaque - Flierl, Ulrike; Schäfer, Andreas (Thrombosis and Haemostasis, 2012)
Chemokines play an important role in inducing chemotaxis of cells, piloting white blood cells in immune surveillance and are crucial parts in the development and progression of atherosclerosis. Platelets are mandatory players in the initiation of atherosclerotic lesion formation and are susceptible targets for and producers of chemokines. Several chemokine receptors on platelets have been described previously, amongst them CX3CR1, the receptor for fractalkine. The unique chemokine fractalkine (CX3CL1, FKN) exists as a soluble as well as a membrane-anchored glycoprotein. Its essential role in the formation of atherosclerotic lesions and atherosclerosis progression has been impressively described in mouse models. Moreover, fractalkine induces platelet activation and adhesion via a functional fractalkine receptor (CX3CR1) expressed on the platelet surface. Platelet activation via the FKN/CX3CR1-axis triggers leukocyte adhesion to activated endothelium, and fractalkine-induced platelet P-selectin is mandatory for leukocyte recruitment under arterial flow conditions. This review summarises the role of fractalkine as a potential local inflammatory mediator which influences platelet activation in the setting of atherosclerosis. Beyond that, aspects of a potential interaction between fractalkine and platelet responsiveness to antiplatelet drugs are described. Furthermore, the possible impact of high-density lipoprotein cholesterol (HDL-C) on atherosclerosis progression, platelet activation and fractalkine signalling are discussed.
Keywords: Fractalkine; platelet activation; atherosclerosis; HDL